Utilizing AlexNet Deep Transfer Learning for Ear Recognition - Almisreb A.A.; Jamil N.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Convolution; Information retrieval; Knowledge management; Problem solving; AlexNet; Convolution neural network; Ear recognition; Fully-connected layers; Human recognition; Nonlinear problems; Problem domain; Transfer learning; Deep learning